The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12876-017-0627-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrogenic effect of PPAR-γ agonists in human intestinal myofibroblasts

Abstract: BackgroundIntestinal fibrosis is a serious complication of inflammatory bowel disease, including Crohn’s disease and ulcerative colitis. There is no specific treatment for intestinal fibrosis. Studies have indicated that peroxisome proliferator-activated receptor- γ (PPAR-γ) agonists have anti-fibrogenic properties in organs besides the gut; however, their effects on human intestinal fibrosis are poorly understood. This study investigated the anti-fibrogenic properties and mechanisms of PPAR-γ agonists on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
2
15
0
1
Order By: Relevance
“…On the other hand, PPARg agonists can decrease fibrogenesis by inhibiting the effects on TGF-b signaling (Kawai et al, 2009). Furthermore, some researchers have suggested that PPARg has both antiinflammatory and anti-fibrotic effects in the bowel (Speca et al, 2016;Koo et al, 2017). In this regard, natural and synthetic ligands of PPARg have been able to improve the fibrotic condition in both preliminary clinical trials and experimental models of intestinal fibrosis (Koo et al, 2017).…”
Section: Anti-fibrotic Effects Of Ppars In Ibdsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, PPARg agonists can decrease fibrogenesis by inhibiting the effects on TGF-b signaling (Kawai et al, 2009). Furthermore, some researchers have suggested that PPARg has both antiinflammatory and anti-fibrotic effects in the bowel (Speca et al, 2016;Koo et al, 2017). In this regard, natural and synthetic ligands of PPARg have been able to improve the fibrotic condition in both preliminary clinical trials and experimental models of intestinal fibrosis (Koo et al, 2017).…”
Section: Anti-fibrotic Effects Of Ppars In Ibdsmentioning
confidence: 99%
“…Furthermore, some researchers have suggested that PPARg has both antiinflammatory and anti-fibrotic effects in the bowel (Speca et al, 2016;Koo et al, 2017). In this regard, natural and synthetic ligands of PPARg have been able to improve the fibrotic condition in both preliminary clinical trials and experimental models of intestinal fibrosis (Koo et al, 2017). PPARg Reduce the state of activation of myofibroblasts and the expression of the main pro-fibrotic molecules as TGF-b, Smad3, IL-13, CTGF, and GSK-3b DSS-induced colitis mice Speca et al, 2016Di Gregorio et al, 2017 J11-Cl (Jasmonate) PPARg Decreases pro-inflammatory cytokines production DSS-induced colitis mice Choo et al, 2015 rSj16 (recombinant secreted protein of Schistosoma japonicum)…”
Section: Anti-fibrotic Effects Of Ppars In Ibdsmentioning
confidence: 99%
“…48 TGF-β1-induced fibrogenesis is also mediated by Smad-independent pathways, including phosphorylation of extracellular signal regulated kinase, c-Jun N-terminal kinase, p38 mitogen-activated protein kinase (MAPK), and AKT. 26,[48][49][50] Another Smad-independent pathway is Ras homolog family member/Rho kinase/actin/myocardinrelated transcription factor/serum response factor (Rho/ ROCK/Actin/MRTF/SRF) pathway. 51,52 TGF-β1-induced activation of Rho and its effector ROCK, which promotes actin polymerization from globular actin to filamentous actin.…”
Section: Cellular and Soluble Mediators Of Fibrosismentioning
confidence: 99%
“…CP-544439-treated mice also have reduced expression of the key adipogenesis regulator PPARγ (120,(122)(123)(124). The antifibrotic effects of PPAR family proteins have been described in different tissue systems (125)(126)(127)(128)(129)(130). MMP-13-mediated regulation of PPAR expression in obese adipose tissue might therefore act as an important molecular switch that determines fibrogenic or adipogenic adipocyte progenitor fate.…”
Section: Collagens and Collagen-cleaving Enzymes In Adipocyte Differementioning
confidence: 99%